Frailty syndrome in the elderly in elderly with chronic diseases in Primary Care - Ingrid Alves Ribeiro; Luciano Ramos de Lima; Cris Renata Grou Volpe; Silvana Schwerz Funghetto; Tânia Cristina Maria Santa Barbara Rehem; Marina Morato Stival
ABSTRACT Objective: To evaluate the frailty syndrome in the elderly nursing diagnosis in elderly with chronic diseases of a health district of the Federal District. Method: A quantitative, descriptive, cross-sectional study was conducted with elderly patients served at the Basic Health Units, who presented arterial hypertension and/or diabetes mellitus. The following were used: a sociodemographic questionnaire, the Mini-Mental State Examination, anthropometric data, evaluation of sarcopenia (measured by body composition), muscle strength and functional capacity, and the identification of NANDA-I nursing diagnosis. A statistical software was used for data analysis. Results: Participation of 78 elderly people, of which 93.6% of had Impaired memory, 93.6% had Impaired physical mobility, 82.1% had Fatigue, 76.9% had Impaired ambulation, 53.8% had Dressing self-care deficit, 43.6% had Activity Intolerance, 35.9% had Social Isolation, 30.8% had Hopelessness, 29.5% had Feeding self-care deficit, 29.5% had Bathing self-care deficit, 12.8% had Toileting self-care deficit, and 10.3% had Decreased cardiac output. Conclusion: The nursing diagnosis Frailty Syndrome in the Elderly allows a multidimensional view of the elderly. Since one factor can cause health problems in several health fields, nurses must intervene early, plan and implement actions in the short and long term.